ASSESSING THE EFFECTIVENESS OF FLIPPED CLASSROOM APPROACH ON LEARNING OUTCOMES AMONG UNDERGRADUATE NURSING STUDENTS: A QUASI-EXPERIMENTAL STUDY (The Research of Medical Science Review, 2024)
The class format can be described as learner-centered or upside-down classrooms where the teacher’s role is decreased in terms of pure information presenting and increased in terms of providing possibilities for using knowledge. Significantly, the flipped classroom approach draws emphasis on both online teaching as well as face to face teaching, This study aimed to assess the Effectiveness of Flipped Classroom Approach on Learning Outcomes among Undergraduate Nursing Students. This was a quasi-experimental study carried out in Khyber Pakhtunkhwa. Data were collected from a total of 50 nursing students of fourth semester. Four months flipped interventions were applied in health assessment class where the knowledge and practices of the students was based. Data were collected using an adopted questionnaire, Most of the participants in this study were male and belonging to urban areas. The findings of the study reported significant mean score difference between pre and post health assessment knowledge (P=0.000) and practices (P=0.004) of nursing students. By employing flipped learning approach, this study revealed that there were enhanced nursing students’ health assessment skills as well as the knowledge. Flipped classroom approach is one of the effective teaching learning strategies in nursing education.